Techniques of color guard - Sloan, Karyn (Philadelphia Mason Crest Publishers, 2003)
Describes the history and techniques of color guards, including music, choreography, flag twirling, rifle twirling, teamwork and pageantry
Includes bibliographical references and index
CHK-1003g donated by Mynette Aguilar
Keywords: Color guards -- Juvenile literature; Marching drills -- Juvenile literature; Color guards; Marching drills